GLOBALIZACIÓN CULTURAL E INVESTIGACIÓN INTERCULTURAL EN PSICOLOGÍA SOCIAL: APUNTES PARA LA PROBLEMATIZACIÓN DE UN VÍNCULO IGNORADO - Pérez Sánchez, Rolando (2023)
Taking into account the current cultural globalization process, the aim of the present article is to provide a critical evaluation of cross-cultural research on social psychology. It begins with a conceptualization of cultural globalization, followed by a critical review of some basic assumptions of cross-cultural research on social psychology. The article ends with some examples of research on this area, which attempt to overcome the traditional model of cross-cultural research, and highlight the need of its reformulation.